Pharmacokinetics of a continuous intravenous infusion of hydromorphone in healthy dogs - Wimbish, Candace; Lynch, Alex M.; Knych, Heather K.; Ueda, Yu; Messenger, Kristen M. (Frontiers in Veterinary Science, 2024)
Dosing recommendations for hydromorphone intravenous constant rate infusion (IV CRI) are derived from simulations following IV bolus administration. While this extrapolated dose regimen has been described clinically, pharmacokinetics (PK) of hydromorphone infusions in dogs are not yet described. The study objective was to describe the PK of hydromorphone in healthy dogs receiving an IV bolus followed by an IV CRI for 48 hours.A prospective, experimental study was performed involving the administration of hydromorphone (0.1 mg/kg IV bolus then IV CRI 0.01 mg/kg/hr over a 48-hour period) to 6 healthy Beagle dogs. Blood samples were collected at 16 time points between 0-58 hours relative to the initial bolus. Plasma hydromorphone concentrations were analyzed by high pressure liquid chromatography with tandem mass spectrometry detection. Pharmacokinetic parameter estimates were obtained with compartmental methods using commercially available software.A two-compartment model with first order elimination was used. At the end of the infusion, median (range) plasma hydromorphone concentrations were 6.8 (5.5-19.6) ng/mL. The median total body clearance was 30.4 (19.8-36.7) mL/min/kg; volume of distribution at steady state was 4.5 (3.2-7.8) L/kg; and terminal elimination half-life was 11.2 (7.6-24.3) hr.Hydromorphone (0.1 mg/kg IV bolus then IV CRI of 0.01 mg/kg/hr) maintained steady-state plasma concentrations above the minimum human analgesic target in healthy Beagle dogs with minimal side effects. Further studies are needed to determine the effective plasma concentrations of hydromorphone in painful dogs.